Introduction to China’s new normal economy - Zhang, Jing; Chen, Jian (Taylor & Francis, 2017)
China’s economic reform has been successful, making it become a major economic power. Largely relied on low-cost investment, cheap and abundant labour and use of natural resources to support growth, China has faced a number of challenges including high debt to GDP, demographic changes and environmental degradation, along with income inequality, corruption and rent-seeking activities. In recent years, China’s economic growth rate has fallen from the historic double-digit rate to 6–7%. Chinese Government has attempted to rebalance its economy to achieve a “new normal” of slower but more sustainable economic development. This special issue aims to raise discussions concerning the ways in which further reform of the Chinese economy can be conducted in the context of challenges and opportunities of the new normal. The issue comprises five papers that exhibit special insights of interest, including the discussions on drivers of economic growth, the role of government policy played in economic growth in the coming decades, the importance of innovation and government institutions in firm performance, the impact of capital structural on firm competitiveness, as well as the relationship between the use of social networks and wages of rural–urban migrant workers.